A Comparative Evaluation of Distance Learning Versus Traditional Teaching Methods in an Associate Degree Nursing Program - Nicoll, Leslie; Steinhacker, Marianne; Ouellette, Teena (Maine Policy Review, 1996)
The policy question addressed by this article is whether distance education works. Are students taught by distance learning disadvantaged relative to their peers in traditional educational settings? The results of this study strongly indicate that distance learning in nursing does work and that significant benefits may result for rural Maine residents if distance learning opportunities are expanded.
Keywords: Maine; distance learning; nursing education